2016
DOI: 10.1039/c5an02031j
|View full text |Cite
|
Sign up to set email alerts
|

Hg2+ detection using a phosphorothioate RNA probe adsorbed on graphene oxide and a comparison with thymine-rich DNA

Abstract: Mercury is a highly toxic heavy metal and many DNA-based biosensors have been recently developed for Hg 2+ detection in water. Among them, thymine-rich DNA is the most commonly used for designing Hg 2+ sensors. However, the thymine-Hg 2+ interaction is strongly affected by buffer conditions. We recently reported a molecular beacon containing phosphorothioate (PS)-modified RNA linkages that can be cleaved by Hg 2+ . In this work, the fluorescence quenching and DNA adsorption properties of nano-sized graphene ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Ono and coworkers have first reported that Hg 2+ can specifically interact with thymine–thymine (T–T) mismatch sites of a DNA duplex, resulting in stable formation of T–Hg 2+ –T complexes with a hairpin structure 39,51,52 . Since then, many works have been developed for the detection of Hg 2+ based on the T–Hg 2+ –T interaction using various types of materials 2 such as carbon nanotubes, 53 quantum dots, 54 graphene, 55,56 silica nanoparticles, 57 gold nanoparticles, 58 silver nanoclusters, 59 and magnetite nanoparticles 60 …”
Section: Introductionmentioning
confidence: 99%
“…Ono and coworkers have first reported that Hg 2+ can specifically interact with thymine–thymine (T–T) mismatch sites of a DNA duplex, resulting in stable formation of T–Hg 2+ –T complexes with a hairpin structure 39,51,52 . Since then, many works have been developed for the detection of Hg 2+ based on the T–Hg 2+ –T interaction using various types of materials 2 such as carbon nanotubes, 53 quantum dots, 54 graphene, 55,56 silica nanoparticles, 57 gold nanoparticles, 58 silver nanoclusters, 59 and magnetite nanoparticles 60 …”
Section: Introductionmentioning
confidence: 99%
“…However, some prepared sensors have much more detection limit to Hg 2+ ion detection in high sensitivity, most of these receptors are difficult to prepare, or the reactions are not cost-effective. Herein, we prepared a fluorescent sensor by organic synthesis, which has some superior as simple operation, low-cost starting material, avoiding by-product, high yield, and in short reaction time [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this Hg 2+ ‐driven T–T mismatch could be easily affected by certain reaction buffer conditions such as temperature, pH, ionic strength, and ion species. [ 21–24 ] Apart from these strategies, DNAzymes have been also generally used based on their specific binding to Hg 2+ . [ 25 ] However, the issue of low catalytic efficiency has limited their downstream applications.…”
Section: Introductionmentioning
confidence: 99%